Analysis of Diabetes Mellitus Drug Planning Using ABC and VEN Methods Based on Value of Use and Investment Value in Pharmacy Warehouse General Hospital Insan Permata Period January - March 2021 - Purwaningsih, Neneng Sri; Senjaya, Ahmad Senjaya; Sucipto, Sucipto Sucipto; Angguni, Melani Angguni (Health and Medical Journal, 2022)
Introduction: According to Basic Health Research in 2018 has collected data on people with diabetes mellitus in Indonesia showing that the prevalence of diabetes mellitus has increased according to the results of blood sugar measurements increased from 6.9 in 2013 to 8.5 in 20181. The hospital carries out a pharmaceutical activity carried out by the Hospital Pharmacy Installation (IFRS). The pharmaceutical work activities is  related to the manufacture, quality control of pharmaceutical preparations, management of pharmaceutical supplies (planning, procurement, receipt, storage, distribution, recording, reporting, destruction/elimination), prescription services, drug information services, counseling, clinical pharmacy in room . Drug planning is carried out to avoid drug shortages by using methods that can be accounted for and the basis for planning that has been determined, including consumption, epidemiology, a combination of consumption and epidemiological methods and adjusted to the available budget 2. Aims: This study aims to classify diabetes drugs using ABC analysis and VEN analysis to help the control of diabetes drugs at Pharmacy Instalation of Insan Permata Hospital. Methods: The methods  is a non-experimental study with retrospective data collection in January - March 2021 in the form of reports on drug names, drug purchases, drug sales and the purchase price of diabetes mellitus drugs at the Insan Permata Hospital. The data were analyzed using the ABC method and the VEN method. Results: The results showed that of the 12 drug items based on use value, there were 44511 units of drugs used, there were 5 groups, namely the AE group there were 2 items, the BE group had 4 items, the CE group had 1 item, the CV group had 3 items and the CN group had 2 items. Based on the total investment value of Rp. 100,274,770. There are 6 groups, namely the AV group has 1 item, the BV group has 1 item, the BE group has 3 items, the CV group has 1 item, the CE group has 4 items, and the CN group has 2 items. Conclusion: After analyzing the 12 items with ABC (Always Better Control)  dan VEN Vital Essensial Non Essensial)  methods, there are 10  items for planning drug procurement in the next period, start april 2021.